Mixed versus pure variants of Desmoplastic Melanoma: The Cleveland Clinic Experience - Conic, Ruzica Z. (Ann Plast Surg, 2018)
BACKGROUND: Desmoplastic melanoma (DM) is a sub-variant of spindle cell melanoma, accounting for less than 4 percent of all cutaneous melanomas. It occurs later in life and is associated with chronic sun exposure. DM prognosis is considered more favorable than other variants, with lower rates of metastasis and higher survival. Recently DM has been further sub-classified into pure and mixed, calling into question surgical management and patient outcomes as well as viability of current nationwide databases without this distinction. METHODS: We identified all patients with a histopathologic diagnosis of desmoplastic melanoma from the Cleveland Clinic electronic melanoma database (n=58) from 1997–2013. Clinical and histopathologic data were collected. Comparison in clinical variables was performed between patients who had pure (n=15) and mixed (n=43) variants of DM. RESULTS: There were no differences in age, gender, location of lesion, Breslow depth, ulceration, or regression. Patients with mixed desmoplastic melanoma were more likely to have lymphovascular invasion (p=0.03) compared to pure desmoplastic melanoma. There was no difference in performance of sentinel lymph node biopsy (p=0.25) or sentinel lymph node positivity (p=0.31) between the two groups. Recurrence was present in 13.3% of pure and 30.2% of mixed patients. Overall Kaplan Meier 3 year survival was 75% for pure and 80% for mixed desmoplastic melanoma (p=0.53). CONCLUSION: Pure and mixed desmoplastic melanomas appear to have similar clinical characteristics and outcomes. This indicates that analysis of national datasets without this sub classification remains viable.